The Effect of Using Digital Flashcards on English Vocabulary Mastery at Seventh Grade Students of SMPN 17 Mataram - Munigarim, Munigarim; Melani, Boniesta Zulandha; Putera, Lalu Jaswadi; Arifuddin, Arifuddin (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study aimed to determine whether there is a significant effect of using digital flashcards vocabulary mastery in grade VII students of SMPN 17 Mataram. Researchers conducted quantitative research using a quasi-experimental method with a quasi-experimental design that is nonequivalent to a control group design. The subjects of this study were 60 seventh-grade students in Smpn 17 Mataram with class VIIA (experimental class) and VIIE (control class). Data collection was carried out using vocabulary tests, namely pretest and posttest. The Test consists of 25 questions. In using digital flashcards, the average value of the pretest in the experimental class is 55.40 while the average value of the posttest is 76.27. While students who do not use the media slightly increased from 53.00 on the pre-test to 60.73 on the post-test. The normality test used is the Kolmogorov-Smirnov Test shows the normal distribution of data. Based on data analysis using independent sample t-test on SPSS version 26. The significance test result is 0.001 which is smaller than the significance level of 0.05. It can be concluded that students who are taught by using digital flashcards as a medium of teaching materials are better than students who do not use any media.